Обоснование расчетных моделей силосных установок - Третьяков, В. Б.; Иванцов, И. И.; Веретельник, Олег Викторович; Атрошенко, Александр Александрович (НТУ "ХПИ", 2013)
This paper describes the results of research of the stress-strained state of a silage for storage of grain and other products. Test problems are considered for corrugated panel's silage for bolted connections, as well as full body design silage. Described the problematic factors for building computational models of the elements of silage.
Keywords: состояние напряженно-деформированное; силос; метод конечных элементов; панели гофрированные